Workshop Standar Opersional Prosedur Pelaksanaan Konseling Guru ke Murid di Lingkup SD Hafizh Al-Qurbah YAJI - Amirullah, Muhammad; fitriana, Fitriana; Aswar, Aswar; Zulfikri, Zulfikri; Rahmi, Sitti (INKAMKU : Journal of Community Service, 2024)
The implementation of this community service activity aims to raise awareness and understanding, as well as improve the ability of teachers at Hafizh Al Qurbah YAJI Elementary School in providing counseling services to students at school as well as providing initial psychological support for students who are experiencing academic, personal and social problems with friends. peers or family. Method of implementing service. The methods used in carrying out this community service activity are lecture, question-answer and resonance methods. Mental health workshop activities are in order to increase the capacity of teachers in providing counseling services to students and parents in the Hafizh Al Qurban YAJI Elementary School environment. This activity was carried out directly (offline) with teachers in all SD Hafizh Al Qurbah YAJI units. This activity was carried out in 3 sessions, namely: 1) the first session was the delivery of material using the lecture method containing an explanation of the definition, form and steps (SOP) in providing counseling to students; 2) The second session continued with exploration and activities related to increasing insight and skills in implementing counseling SOPs; and 3) the third session was carried out with applied coercion in carrying out the stages, steps and procedures of counseling. The level of success in community service activities is measured through indicators of the process of involvement and increasing insight carried out by Hafizh Al Qurban Elementary School teachers in providing counseling services to students and parents.